2018
DOI: 10.1371/journal.pntd.0006618
|View full text |Cite
|
Sign up to set email alerts
|

Dengue infection in India: A systematic review and meta-analysis

Abstract: IntroductionDengue is the most extensively spread mosquito-borne disease; endemic in more than 100 countries. Information about dengue disease burden, its prevalence, incidence and geographic distribution is critical in planning appropriate control measures against dengue fever. We conducted a systematic review and meta-analysis of dengue fever in IndiaMethodsWe searched for studies published until 2017 reporting the incidence, the prevalence or case fatality of dengue in India. Our primary outcomes were (a) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
143
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 155 publications
8
143
1
4
Order By: Relevance
“…While dengue positivity was high in all age groups, most laboratory confirmed patients were older than 20 years. This finding is consistent with the meta-analysis of published studies from India until 2017 which reported the mean age of laboratory confirmed dengue patients to be 22 years (Ganeshkumar et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…While dengue positivity was high in all age groups, most laboratory confirmed patients were older than 20 years. This finding is consistent with the meta-analysis of published studies from India until 2017 which reported the mean age of laboratory confirmed dengue patients to be 22 years (Ganeshkumar et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that dispersal of DENV-2 between Africa and India has occurred more than once. Globalization has probably facilitated the introduction of the Indian DENV to Kenya, as Kenya along with other African countries interacts actively with India for trade and travel [47], and India is hyperendemic for DENV [48].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive fluid administration will cause volume overload and pulmonary oedema, thus increasing mortality. 1, 3 Increased mortality has been seen in many previous outbreaks (as high as 25% in south India during 2008), 6 which could be due to improper fluid management.…”
mentioning
confidence: 99%
“…Nepal should think ahead by learning lessons from the countries who suffered the onslaught of dengue in the past, 5,6 and apply lessons learnt to effectively combat the disease in future by formulating awareness…”
mentioning
confidence: 99%